2007
DOI: 10.17221/2028-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of feeding with immunity and parasitic infection: a review

Abstract: Authors overlook the recent findings in the field of the complex interrelationship among nutrition, immune status and parasitic infestation. After summarizing the general characteristics of the active immune system, they describe the first period of the systemic immune response, the acute phase reaction. The cause of drastical decrease in serum zinc concentration is redistribution into the liver and lymphocyte metallothioneins. Immune deficiency correlates only indirectly with the nutrition. Ingestion of feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 60 publications
0
32
0
1
Order By: Relevance
“…It is generally believed that younger animals show clinical symptoms of gastrointestinal parasitism during their first challenge, may accumulate heavy parasitic burdens and subsequently develop resistance under favorable conditions (Soulsby, 1982;Regassa et al, 2006;Mbaya et al, 2009). However, certain conditions such as pregnancy and parturition in female, nutritional stress and concurrent infection, may compromise immunity and exacerbate gastrointestinal parasitism in adult ruminants (Fakete and Kellems, 2007), hence the finding of higher prevalence in adult than young sheep. Male animals are also known to have high natural tendencies of acquiring diseases generally because they tend to move in search of mates for courtship and breeding purposes.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that younger animals show clinical symptoms of gastrointestinal parasitism during their first challenge, may accumulate heavy parasitic burdens and subsequently develop resistance under favorable conditions (Soulsby, 1982;Regassa et al, 2006;Mbaya et al, 2009). However, certain conditions such as pregnancy and parturition in female, nutritional stress and concurrent infection, may compromise immunity and exacerbate gastrointestinal parasitism in adult ruminants (Fakete and Kellems, 2007), hence the finding of higher prevalence in adult than young sheep. Male animals are also known to have high natural tendencies of acquiring diseases generally because they tend to move in search of mates for courtship and breeding purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Fekete and Kellems (2007) reported that zinc has both specific and nonspecific roles in the immune defence mechanism. Zinc regulates the maturation and function of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is the reason why the parasite might restrict itself for de novo synthesis of fatty acids. Parasites normally do not harm host but their high nutritional requirement for growth and reproductive purpose cause nutritional depletion in host which responsible for disease condition in the host (Fekete and Kellems 2007).…”
Section: Polyunsaturated Fatty Acids (Pufa)mentioning
confidence: 99%